The oral microbiota and gestational diabetes mellitus - Corrêa, Jôice Dias; Faria, Giovanna Araújo; Fernandes, Leticia Ladeia (Frontiers in Clinical Diabetes and Healthcare, 2023)
Gestational diabetes mellitus (GDM) is one of the most frequent endocrine conditions during pregnancy. GDM is linked to adverse pregnancy outcomes and has implications for maternal health. Studies have demonstrated the link between pathogenic periodontal bacteria, glycemic control, and the risk of diabetes. The objective of the current study is to perform a mini-review of the available literature on the potential changes in the oral microbiota of women with GDM. The review was conducted by two independent reviewers (LLF and JDC). Indexed electronic databases (PubMed/Medline, Cochrane Library, Web of Science, and Scopus) were searched, including articles published in English and Portuguese. A manual search was also performed to identify related articles. The oral microbial community of pregnant women with GDM is unique from that of healthy pregnant women. The majority of the alterations found in the oral microbiota of women with GDM point to a pro-inflammatory environment with high levels of bacteria associated with periodontitis (Prevotella, Treponema, anaerobic bacteria) and a depletion of bacteria associated with periodontal health maintenance (Firmicutes, Streptococcus, Leptotrichia). More well-designed studies differentiating between pregnant women with good oral health and those with periodontitis are needed to ascertain which differences are due to GDM or periodontitis.